Promosi dan Kepercayaan Konsumen Pengaruhnya Terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan Sebagai Variabel Moderating - Maria Goreti Anul; Uju Suji'ah (Universitas Muhammadiyah Pontianak, 2026)
Customer loyalty in e-commerce is influenced by various marketing factors, yet the roles of promotion and consumer trust remain inconsistent. This study examined the effects of promotion and consumer trust on customer loyalty, with customer satisfaction as a moderating variable, among 100 Shopee users from Manggarai Regency studying in Yogyakarta using purposive sampling and SPSS 27. The results show that consumer trust significantly affects customer loyalty, whereas promotion does not. Promotion and consumer trust jointly influence customer loyalty. Customer satisfaction moderates the effect of promotion but not consumer trust. These findings highlight the importance of strengthening trust and satisfaction to improve customer loyalty.